Essential phospholipids: old physical substances – new production technology - Yu. P. Uspensky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
The aim of review. To present technological innovations in production of new drugs on the basis of essential phospholipids (EPL)Original positions. The positive effect of EPL is known for over 100 years. For over 50 years commercial drugs on a basis EPL are applied, their efficacy is proven by numerous clinical and experimental studies. However, traditionally used technologies of treatment of EPL substance by active oxygen at production effecting drugs are not optimal, as they are accompanied by formation of hydroperoxides having potential toxicity. The alternative method used at production of new drug on EPL basis (RESALUT Pro), provides treatment of phospholipid substances by liquid nitrogen that allows to keep beneficial properties of natural (native) product.Conclusion. The new technology utilised by treatment of agent on EPL basis (RESALUT Pro), is progressive, promoting improvement of safety profile and expected clinical effect.